O bioma Pampa como temática de investigação no ensino básico no município de Uruguaiana - RS - Castro, Luis Roberval Bortoluzzi (2018)
The present research deals with a qualiquantitative investigation, developed in three public schools of complete basic education, located in the city of Uruguaiana-RS. The work was based on the investigation of the perception both of finalist students of the stages of elementary education II, and high school on the Pampa biome theme in order to verify how they perceive the environment in which they live by completing each of the stages of basic education (BE). Since BE educational guidelines dictate that content should be related to the regions in which students live, in addition to pointing out what skills and abilities must be acquired at the end of each stage of BE. Considering that the most used resource currently in Brazilian education is the school books (SB) due to accompanying the student of literacy until the end of elementary education, this material was also investigated, having selected the Science and Biology LDs most used in the municipality, in which the Pampa biome approach was analyzed. The results of the research indicate that there were no significant differences between the information of the three schools, however, indicate that students have a superficial perception of the Pampa biome because the answers are inadequate and fragmented and suggest a lack of contextualization in the school environment, where the contents do not catch the attention of the students that in turn are not perceived in their own context. When analyzed, the SB indicated that the Pampa was the least discussed Brazilian Brazilian biome, with summary information and indicate that the biome is for livestock and agriculture without pointing out important biological information. Allowing to infer that SB do not provide contextualisation, since they do not approach the Pampa in a satisfactory way. Finally, the study suggests that similar investigations should follow at all stages of teaching, as well as the accomplishment of interventions with the students and with the educators with continuous formations that propitiate a relation of greater knowledge on the subject, so that this results in a greater involvement of students with the natural environment in which they live.